Articulação e ornamentação nas Sonatas K18 e K30 de Domenico Scarlatti: um estudo autoetnográfico - Vieira, Uaná Barreto (2018)
This artistic research is an autoethnographic study that aims to describe the interpretative construction of Domenico Scarlatti’s Sonatas K18 and K30 focusing on articulation and ornamentation. This research was guided by the methodological models by Adams et al. (2015) and Anderson (2006). The process of construction of an interpretations reported in this work was made possible by means of the use of a diary, the interaction with a bibliography about the baroque style, the pursuit for interpretive inspiration by listening to recordings and the understanding of my artistic experience in popular music as an element of performative creativity stimulant. Through the autoethnographic process, a set of ornaments and articulation that supported the construction of my interpretation were noted to the score.